Critical factors for oil palm plantation workers acceptance and use of mechanization technovation tools - Ezrin Hani, Sukadarin; Nur Syazwani, Mohd Nawi; Baba, M. Deros; Norani, Nordin; Mohd Nizam A., Rahman (PressAcademia Procedia, 2017)
Oil palm plantation workers, still rely on manual tools and using mechanization technovation tools has been big issues as they rejected to use. Thus, in emphasizing technovation tools in a human activity, this study aims to examine several factors influencing acceptance and use technovation machine tools in Malaysia based on the revised Unified Theory of Acceptance and Use of Technology (UTAUT) model. A total of 126 oil palm plantation workers answer the questionnaire. This model was analyzed using SPSS technique and conducting reliability test, correlation analysis and regression analysis. The results reveal that performance expectancy, facilitating condition and intention to use were supported as important factors to accept and use of technovation. However, effort expectancy and social influence have been rejected because not significantly influence intention to use technovation. The results of study give implications and suggestions to future researchers and practitioners in order to address problems regarding technovation acceptance.